Research on the Characteristics of Coal Bump and Monitoring and Early Warning in Hujiahe Coal Mine - Fei Yu; Tong Zhang; Zhen Wei (Geofluids)
Under the high intensity mining disturbance, coal bump is easily triggered by the sudden release of large amount of elastic energy contained in the coal body, which seriously affects coal mine safety production. Triaxial experiments were used to study the damage characteristics of coal samples subjected to loading at the 401103 working face of Hujiahe coal mine, and the critical value of peak strength of coal samples was investigated. Based on the characteristics of the mechanical damage behavior of coal samples obtained from the triaxial experiment, the statistics of the occurrence of coal bump events at the 401103 working face were conducted through numerical simulation and field monitoring to study the areas that need to be focused on prevention and control, with a view to providing basic research for deep coal mining. The results show the following: (1) the strength of coal samples is “weakened” by stress loading, and the fracture penetrates the coal body interface leading to the formation of tensile-shear damage of coal samples. The value of the damage variable for the coal sample in the initial damage stage is 0; at the damage stabilization stage, the values of damage variables were derived to be located at 0.03~0.14. The bearing capacity of the coal sample decreases rapidly during the accelerated development period. (2) According to the simulation and field monitoring, it is known that 0~100 m in front of the coal mining face belongs to the key monitoring area. (3) With the advancement of the working face, different coal pillar widths have obvious effects on the vertical stress, and stress increase and decrease zones appear on both sides of the coal column, and the peak stress shows the characteristics of increasing first and then decreasing with the advancement of the working face. The width of the working face has a great influence on the change of vertical stress. When the sensitivity of the vertical stress to the width of the working face increases, the stress concentration phenomenon will occur, and a large amount of elastic energy gathered in the coal body is suddenly released to induce coal bump.